Photoinduced modification of surface states in nanoporous InP - Lloyd-Hughes, J; Mueller, S; Scalari, G; Bishop, H; Crossley, A; Enachi, M; Sirbu, L; Tiginyanu, I (2012)
Porous honeycombs of n-type InP were investigated by terahertz time-domain and x-ray photoemission spectroscopies. After photoexcitation the dark conductivity was found to increase quasi-irreversibly, recovering only after several hours in air. The calculated electron density for different surface pinning energies suggests that photoexcitation may reduce the density of surface states. © 2012 American Institute of Physics.